Colistin-Resistant mcr-1-Positive Escherichia coli on Public Beaches, an Infectious Threat Emerging in Recreational Waters - Fernandes, Miriam R. (Antimicrob Agents Chemother, 2017)
The emergence and rapid spread of colistin-resistant Escherichia coli carrying the mcr-1 gene have generated an urgent need to strengthen surveillance. We performed a meticulous investigation of strains of this sort, which resulted in the identification of international clones of E. coli carrying IncX4-plasmid-mediated mcr-1 and bla(CTX-M) genes in recreational waters of public urban beaches in cities with high tourist turnover, highlighting a new environmental reservoir.